Identification of Linomide Derivatives as Potential Anticancer Therapeutics using Molecular Docking Studies - Borges e Soares, Giselle A.; Bhattacharya, Tanima; Mamledesai, Shivalingrao; Ai, Zhaoquan; Hasan, Alexandru Madalin; Cavalu, Simona (Frontiers in Pharmacology, 2022)
12 analogs bearing a structural similarity to linomide, a bonafide anticancer agent were synthesized wherein substituted dianilides were subjected to a cyclization reaction to yield 4-hydroxyquinolin-2(1H)-ones that were further subjected to a Mannich reaction to yield 4-hydroxy-3-(substituted-1-ylmethyl) quinolin-2(1H)-one analogs. Characterization was performed using IR, 1H NMR and 13C NMR spectral analysis. Subsequently, docking studies and in vitro anticancer studies revealed that Compound 3b-2 showed maximum cytotoxicity with IC50 values of 1.539 μM/mL and 1.732 μM/mL against A549 and K562 cell lines respectively and showed the highest MolDock Score of -110.2253 amongst all analogs tested. Our computational and biological data thus sheds light on the cytotoxic ability of these derivatives and warrants future studies that can possibly lead to the development of potent anticancer therapeutics.